Analisis Pengaruh Peningkatan Penerimaan Pajak Restoran Terhadap Pendapatan Asli Daerah Kota Bekasi - Zaenal Abidin; Vivi Cindria; Taufik Hidayat (Jurnal Pajak dan Bisnis, 2020)
Regional original income is a very important revenue sector for the sustainability of regional development. Restaurant Tax is one of the Regional Taxes that contributes to the budget that needs to be optimized in order to achieve taxpayer compliance, the level of taxpayer compliance, especially restaurant taxpayers is an obstacle in the absorption of Regional Original Income, where not all taxpayers are aware of their tax obligations, this clearly must The attention of the Bekasi City Government is to provide tax knowledge so that people are aware of their rights and obligations as citizens. This study aims to determine the effect of increasing restaurant tax revenue on Bekasi City's original revenue in 2017 to 2020. And to find out the implementation of restaurant tax collection, obstacles in collecting restaurant taxes and the efforts made to overcome these obstacles. The research methodology carried out by the author is data collection techniques, namely collecting data with the stages of literature study, field study, observation, and interviews with resource persons related to research problems.